Pengaruh Craving dalam Pencapaian Kondisi Clean and Sober Pecandu Narkotika - Leo Seno Pranoto; Yulianti Dwi Astuti (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2006)
Craving in many cases can bring a recovery drug addict return to an active drug addict again. This research aimed to comprehend the craving process that influence the drug addict to achieve the condition called clean and sober.  Data were gathered from 4 subjects who have been experiencing problem with drug addiction which reside in Yogyakarta and 1 informan who has been working as their counsellor for these past 5 years. Interview and observation were used to collect data.According to the data obtained, this research was able to identify some findings: Category of craving was consisted of eight themes: definition of craving, the forming of craving condition, condition to active drug addict, condition to passive drug addict, trigger-subject interaction, trigger-object interaction, sublimation-positive factor, sublimation-negative factor. There were conditions which always emerge in answers of all subjects especially in category relapse, clean and sober, and the craving. This condition was (personal) self controlKey words: Craving, clean and sober, drug addict